Caseous Abscess in a Shingleback Lizard (Tiliqua rugosa) with Klebsiella sp. Infection - Govendan, Puveanthan Nagappan; Steven Dwi Purbantoro; Sunusi, Sulham; Christiani, Zefanya; Mukti, I Made Beratha; Batan, I Wayan; Raharjo, Slamet (Journal of Advanced Veterinary Research, 2022)
An adult male shingleback lizard (Tiliqua rugosa), weighing 700 grams, was presented with a swelling growth on the left lobe of the head. Â Clinical examination indicated a mass growth, and the lizard was diagnosed with caseous abscess accumulation. Surgical intervention was performed to remove the caseous abscess. Post-surgery treatment consists of enrofloxacin, meloxicam, tramadol, multivitamin, and topical antibiotic cream. Laboratory bacterial culture from the removed caseous abscess revealed Klebsiella sp. infection. Six months after the surgery, the shingleback lizard was presented with no swelling reoccurrence in a clinical healthy condition. Â